Determinants of the Food Security Status of Households Receiving Government Grants in Kwakwatsi, South Africa - Sekhampu, Tshediso Joseph (Mediterranean Journal of Social Sciences, 2013)
This study attempts to estimate the food security status and identify the determinants of food security among householdsreceiving government grants in a township of Kwakwatsi, South Africa. The results are based on a household survey usingquestionnaires. A Logistic regression model was estimated based on this data with the household food security status (that isfood secure and insecure) as the dependent variable and a set of demographic variables as explanatory variables. It wasfound that about 38 per cent of the sampled households are food secure. The results of the regression analysis showed totalhouseholdincome, household size, employment and marital status of the household head, employment status of the spouse asimportant determinants of food security in the area. Household size and the marital status of the head of household werenegatively associated with household food security. The age, gender and educational attainment of the household head werenot significant predictors of household food security status. This study makes a contribution to the understanding of thedynamics of households dependent on government grants by modelling the factors which determine food security and may actas reference source for policy planning purposes.